Hermeneutika Qurâni dan Perbedaan Pemahaman dalam Menafsirkan al-Qurân - Abd. Hadi (Islamica: Jurnal Studi Keislaman, 2011)
To interpret al-Qurân means to understand the hidden meaning of this revealed text. This is the essence of hermeneutics. It is about unearthing the implicit truth and making it explicit. Hermeneutics is also a method to read the symbols otherwise not known by the common readers. This method is not only concerned with the literal understanding of the text, but also with the contextual and rational meaning of it by taking into account the horizons around which the text is produced. By horizon it is meant, the nature of the text, the mind and logic of the author and the universe of the reader. This paper deals with the idea of what we call the Qurânic hermeneutics. By that we mean the method that has been developed by the competent scholars of the Qurânic exegesis over time. We assume that the nature of the Qurân necessitates that this holy text cannot be interpreted unilaterally, as it were. That the Qurân uses the symbolic words and expression makes it open to be inter preted differnently by the different scholars. We are interested in exploring further the nature of this Qurânic hermeneutics and the various outcomes produced by it.